Dual‐System Use and Intermediate Health Outcomes among Veterans Enrolled in Medicare Advantage Plans. (6th April 2015) - Cooper, Alicia L.; Jiang, Lan; Yoon, Jean; Charlton, Mary E.; Wilson, Ira B.; Mor, Vincent; Kizer, Kenneth W.; Trivedi, Amal N.
Abstract : Objective: The concurrent use of multiple health care systems may duplicate or fragment care. We assessed the characteristics of veterans who were dually enrolled in both the Veterans Affairs (VA) health care system and a Medicare Advantage (MA) plan, and compared intermediate quality outcomes among those exclusively receiving care in the VA with those receiving care in both systems. Data Sources/Study Setting: VA and MA quality and administrative data from 2008 to 2009. Study Design: We used propensity score methods to test the association between dual use and five intermediate outcome quality measures. Outcomes included control of cholesterol, blood pressure, and glycosylated hemoglobin among persons with coronary heart disease (CHD), hypertension, and diabetes. Data Collection/Extraction Methods: VA and MA data were merged to identify VA‐only users ( n  = 1, 637) and dual‐system users ( n  = 5, 006). Principal Findings: We found no significant differences in intermediate outcomes between VA‐only and dual‐user populations. Differences ranged from a 3.2 percentage point (95 percent CI: −1.8 to 8.2) greater rate of controlled cholesterol among VA‐only users with CHD to a 2.2 percentage point (95 percent CI: −2.4 to 6.6) greater rate of controlled blood pressure among dual users with diabetes. Conclusions: For the five measures studied, we did not find evidence that veterans with dual use of VA and MA care experienced improved or worsened outcomes as compared with veterans who exclusively used VA care.